Pelatihan Mendeley untuk Penulisan Sitasi Karya Ilmiah bagi Mahasiswa di Universitas Nahdlatul Ulama Lampung - Wardany, Kusuma; Mariana, Erni; Utami, Endang Sri; Qomariyah, Siti; Rosyidah, Ummi; Kinasih, Ayang (Pakis Journal Institute, 2025)
For academics such as lecturers, students, and researchers, writing scientific articles is a mandatory task that essentially involves citing or including the work of other authors. This community service initiative aims to train students in using the Mendeley reference manager. Citing sources correctly can be challenging due to the need to understand specific citation styles, resulting in frequent errors. However, the Mendeley application usually ensures citation accuracy for scientific article writers. Therefore, Mendeley training is crucial for students. The limited face-to-face training session, enthusiastically attended by 33 participants, provided new insights into scientific writing and streamlined literature searches. This training is expected to empower Elementary School Teacher Education students to manage scientific references effectively with Mendeley, ultimately improving their ability to produce high-quality scientific articles.